Meritokrasi dalam Bayang-Bayang Birokrasi : Studi Komparatif Sistem Administrasi Publik Indonesia dan Singapura - Tatimmatunni'Amah; Aminullah Aminullah (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
This article examines how meritocracy is institutionalized within the public administration systems of Indonesia and Singapore and how it affects public service quality. Using a descriptive–comparative library research design, the analysis focuses on four dimensions: bureaucratic structure, governing system and political influence, administrative reform and merit mechanisms, and implications for service delivery. The findings indicate that Indonesia’s bureaucracy remains highly hierarchical and decentralized, creating uneven institutional capacity and allowing electoral–political dynamics to influence appointments and rotations, which weakens consistent merit implementation. In contrast, Singapore operates a streamlined and centrally coordinated bureaucracy supported by high political stability, rigorous competency-based recruitment and promotion, transparent performance management, and competitive remuneration, enabling merit principles to be applied more consistently. These differences translate into more uniform and efficient public services in Singapore, while Indonesia continues to experience variability across regions and sectors. Strengthening merit enforcement, oversight, and professional culture is therefore crucial to improve the effectiveness and equity of public services in Indonesia.